Review of the Conference on Security and Cooperation in Europe: 40 years after Helsinki - Dimitrijević Duško (Međunarodni Problemi, 2015)
The paper deals with the genesis of the Conference on Security and Cooperation in Europe (CSCE) as the important pan-European forum for addressing security issues during the Cold War era, and, secondly, analyses the dynamics of institutional changes that led to establishment of the Organisation for Security and Cooperation in Europe (OSCE). As an active factor in the process of détente and the easing of tensions between the then USSR and the United States, the CSCE was the place in which were flowing all initiatives related to overcoming the security problems in bipolar Europe. The paper provides a brief of negotiation process that produced the Helsinki Final Act of 1975, an international political document that laid down the basic principles of interstate relations and political commitments in a number of areas, from military-political security, to economic and environmental co-operation and human rights. The author concludes that the role of the OSCE is likely to stagnate in the 21st century, for it will not be sufficiently capable to influence Euro-Atlantic and Euroasian affairs, and to maintain its function as an important consultative and negotiating mechanism, as well as a platform for regional security and cooperation. [Projekat Ministarstva nauke Republike Srbije, br. br.OI179023: Srbija u savremenim međunarodnim integrativnim procesima - spoljnopolitički, međunarodni, ekonomski, pravni i bezbednosni aspekti]